Preparations and Challenges Upon the Implementation of PSAK 55: A Case Study of Rural Banks (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2022)
Purpose: This study aims to analyze the preparations and challenges of PSAK 55 implementation regarding Institutional Logics Theory and Diffusion Theory of Innovation that underlined the ac- tor’s decision to implement PSAK 55 in rural banks.Method: This study uses descriptive qualitative methods through questionnaires and interviews analyzed with content, thematic, and constant comparative analysis. study uses descriptive qualita- tive methods through questionnaires and interviews analyzed with content, thematic, and constant comparative analysis.Finding: This study reveals the factors that influence the actors’ decisions in this implementation, such as the existence of dominant logic in which rural banks must comply with regulations, but ac- tors are concerned more about the effectiveness of PSAK 55. Moreover, this study found the prepa- rations to implement PSAK 55, such as updating internal regulations and systems, human resources, socialization and training. Whereas, the expected challenges are the limitations in analyzing objec- tive evidence of impairment, calculating the fair value of collateral and value of future cashflow.Novelty: This study differs from prior studies because it focused more on discussing the prepara- tions and challenges using Institutional Logic Theory, while the previous discussed only the imple- mentation of PSAK 55 in commercial banks and actors’ behavior upon the credit restructuring. The implication of this research is to provide solutions to rural banks, so there would be no decoupling practice.